The Parents Role to Prevention of Drug Abuse in Teenager - Annisa Nisa Anis; Shomedran Shomedran (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
The problem of drug abuse is a major problem in Indonesia, especially in adolescents, overcoming the problem of drug abuse requires the role of parents. This study aims to determine the role of parents in preventing drug abuse for adolescents in the Teladan Village, South Bangka Regency which is studied from 5 indicators of the role of parents, namely the role of parents in educating, supervising, guiding, communicating, and protecting adolescents in drug abuse. This type of research is descriptive research with a qualitative approach. The selection of informants used purposive sampling technique, so that the number of informants in this study was 5 people. The collection technique was obtained from primary data, namely parents in the Teladan Village RW 04 and 05 by interviewing, observing, and documenting. The results of the study indicate that the role of parents in preventing drug abuse is more about religious education, making adolescent social rules, conducting open and closed communication, providing supervision, and protecting adolescents with the use of social media and adolescence. However, in carrying out their roles there are often debates between teenagers, and teenagers are more closed to their parents. This study suggests to always have good communication, provide wise rules and pay attention to the development of adolescents in order to avoid drug abuse.Keywords: Role of Parents, Adolescents, Drug Abuse.